Trammel's Trace : The First Road to Texas from the North - Pinkerton, Gary L., 1954- (Book collections on Project MUSE., 2016)
Trammel's Trace tells the story of a borderlands smuggler and an important passageway into early Texas. Trammel's Trace, named for Nicholas Trammell, was the first route from the United States into the northern boundaries of Spanish Texas. From the Great Bend of the Red River it intersected with El Camino Real de los Tejas in Nacogdoches. By the early nineteenth century, Trammel's Trace was largely a smuggler's trail that delivered horses and contraband into the region. It was a microcosm of the migration, lawlessness, and conflict that defined the period. By the 1820s, as Mexico gained indepe.